Advanced management of separated root canal instruments in mandibular molars: bypass technique combined with diode laser irrigation: Penanganan lanjut dari instrumen saluran akar yang patah pada gigi molar rahang bawah: teknik bypass dikombinasikan dengan irigasi laser diode - Hikmah, Noor; Lestari, Dian Bunga (Makassar Dental Journal, 2025)
The bypass technique allows for optimal cleaning and shaping of the root canal around the fractured instrument, thereby in-creasing the chances of successful treatment. A 25-year-old woman came to RSGMP Unhas complaining of a lump on her lo-wer right posterior gum and had undergone root canal treatment but it was not yet complete. Intraoral examination of tooth 46 revealed vitality test (-), percussion (-), and palpation (-) with a 3 mm diameter fistula on the lingual side. Radiographic exami-nation of the fractured instrument showed widening of the periodontal ligament at the apical third of the mesial root canal. The initial diagnosis was incomplete therapy accompanied by chronic apical abscess. The patient was scheduled for endodontic treatment using the bypass technique. Root canal preparation was performed using the bypass technique with K-files numbered 8 to 20, followed by preparation using Protaper Gold F4 and disinfection with 5.25% NaOCl, as well as activation using a diode laser for 20 seconds in 3 cycles. Ca(OH)2 was placed as a root canal medication for 2 weeks. Obturation was performed using the hydraulic condensation technique with a bioceramic sealer. The patient showed no symptoms and experienced stable im-provement. Monitoring for 3 months is ongoing. It is concluded that the careful application of the bypass technique, supported by a diode laser, provides a reliable and effective method for addressing the challenge of fractured endodontic instruments.